2018
DOI: 10.3389/fimmu.2018.01674
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Leprosy—From Classic Immune-Related Candidate Genes to Hypothesis-Free, Whole Genome Approaches

Abstract: Genetics plays a crucial role in controlling susceptibility to infectious diseases by modulating the interplay between humans and pathogens. This is particularly evident in leprosy, since the etiological agent, Mycobacterium leprae, displays semiclonal characteristics not compatible with the wide spectrum of disease phenotypes. Over the past decades, genetic studies have unraveled several gene variants as risk factors for leprosy per se, disease clinical forms and the occurrence of leprosy reactions. As expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 88 publications
0
21
0
1
Order By: Relevance
“…population. Several studies have consistently reported the involvement of HLA class II alleles, mostly HLA-DRB1 alleles, as key genetic factors controlling susceptibility to various forms of leprosy [11,18,[39][40][41]. A recent HLA imputation-based meta-analysis in the Chinese population identified HLA-DRB1 and HLA-DQA1 alleles and specific amino acids of HLA-DRβ1 as independent protective factors for leprosy [39].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…population. Several studies have consistently reported the involvement of HLA class II alleles, mostly HLA-DRB1 alleles, as key genetic factors controlling susceptibility to various forms of leprosy [11,18,[39][40][41]. A recent HLA imputation-based meta-analysis in the Chinese population identified HLA-DRB1 and HLA-DQA1 alleles and specific amino acids of HLA-DRβ1 as independent protective factors for leprosy [39].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…From the early observations of familial clusters of leprosy cases to recent whole-exome sequencing studies identifying genetic variants associated with leprosy, there is strong evidence to suggest that the development of this disease is under tight human genetic control [2,5]. Genetic studies, including positional cloning analyses [6][7][8], genomewide association studies [9][10][11][12][13][14][15], and, more recently, whole-exome sequencing [16] have identified several susceptibility loci for leprosy (reviewed in [17] and [5]), and have demonstrated the involvement of both innate and adaptive immune responses in this disease [18]. Almost all the susceptibility loci identified in genome-wide studies to date were found in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…From the early observations of familial clusters of leprosy cases to recent whole-exome sequencing studies identifying genetic variants associated with leprosy, there is strong evidence to suggest that the development of this disease is under tight human genetic control (2, 5). Genetic studies, including positional cloning analyses (6-8), genome-wide association studies (9-15), and, more recently, whole-exome sequencing (16) have identified several susceptibility loci for leprosy (reviewed in (17) and (5)), and have demonstrated the involvement of both innate and adaptive immune responses in this disease (18). Almost all the susceptibility loci identified in genome-wide studies to date were found in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…However, investigating the immune response elicited by M. leprae remains a particular challenge, due to its extreme dependence on the human host. Genetic disease association studies shed light on a wide range of aspects from the onset of infection to disease cornification, by uncovering genes whose protein products may play pivotal roles in this pathology (48). This has been the case for several genes of the lectin pathway of complement; those encoding PRMs, MBL2 (3) (4) (14), FCN1 (5), FCN2 (4) and FCN3 (9) and the serine protease MASP2 (6) and the possible receptor for MBL encoded by CR1 (10).…”
Section: Discussionmentioning
confidence: 99%